A three-dimensional porous chitosan / coal-based activated carbon composite sponge and its preparation method and application in extracting uranium from seawater
By preparing three-dimensional porous chitosan/coal-based activated carbon composite sponge rich in hydroxyl, amino and phosphate groups, the problem of vanadium competition in uranium extraction in seawater is solved, the adsorption efficiency and selectivity of uranium is improved, and efficient Uranium extraction.
Patent Information
- Application Number
- CN202210007345.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-06
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2042-01-06
AI Technical Summary
When extracting uranium from seawater in the prior art, fierce competition in vanadium leads to low uranium extraction efficiency and insufficient stability and selectivity of materials, making it difficult to effectively solve the interference of ultra-low uranium concentration and polymetal ions.
Three-dimensional porous chitosan/coal-based activated carbon composite sponge is used as the adsorption material, and is prepared through alkali activation, hydrothermal reaction, phosphorylation and other steps to form a composite sponge rich in hydroxyl, amino and phosphoric acid groups on the surface, thereby increasing the adsorption capacity of uranium and selective.
It significantly improves the adsorption capacity and selectivity of uranium, and can effectively select adsorption of uranium in vanadium-uran mixed solution, reducing the competitive effect of vanadium and improving the extraction efficiency of uranium.
Smart Images

Figure CN114471477B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adsorption materials, and in particular to a three-dimensional porous chitosan / coal-based activated carbon composite sponge and a preparation method and application thereof. Background Art
[0002] Nuclear energy is a safe, economical, efficient and clean energy, and is an important energy option for mankind to cope with climate change. Uranium is the most critical raw material for nuclear power generation, so uranium mining and recycling are crucial to the development of nuclear power. In order to cope with the severe shortage of uranium reserves on land, the development of marine uranium resources to meet the growing consumption of nuclear power fuel has attracted widespread attention from countries with nuclear energy demand.
[0003] Seawater holds more than 4.5 billion tons of uranium, a thousand times the amount of terrestrial ores, and can provide a potentially nearly unlimited supply of fuel for the nuclear energy industry. In addition, extracting uranium from seawater has the potential to reduce the negative environmental impacts of the mining process. However, the ultra-low uranium concentration (about 3.3 ppb) and the large amount of coexisting metal ions in seawater have severely restricted the development and utilization of uranium resources. In recent decades, researchers around the world have tried various methods to recover uranium from seawater and aqueous solutions, such as adsorption, ion exchange, and photocatalysis. Among these technologies, adsorption is the most suitable method for extracting uranium from seawater, considering the uranium extraction rate, material stability, and selectivity for uranyl ions, and it is also one of the methods with great prospects for industrial development.
[0004] Amidoxime-functionalized adsorbents are currently the latest materials for collecting uranium from seawater. However, marine experiments have shown that vanadium is preferentially extracted over uranium and many other cations. In particular, the fierce competition of vanadium in uranium seawater extraction remains a great challenge. Summary of the invention
[0005] The purpose of the present invention is to provide a three-dimensional porous chitosan / coal-based activated carbon composite sponge and a preparation method and application thereof. The three-dimensional porous chitosan / coal-based activated carbon composite sponge of the present invention can selectively adsorb uranium.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a three-dimensional porous chitosan / coal-based activated carbon composite sponge, comprising the following steps:
[0008] Activating the coal powder with alkali to obtain activated coal;
[0009] Placing the activated coal in a KOH aqueous solution for hydrothermal reaction to obtain coal-based activated carbon;
[0010] The coal-based activated carbon, methane sulfonic acid and P2O5 are mixed and phosphorylated to obtain phosphorylated coal-based activated carbon;
[0011] A phosphorylated chitosan aqueous solution, an acetic acid solution of chitosan, phosphorylated coal-based activated carbon and an NH4HCO3 solution are mixed, the resulting mixture is frozen, the resulting frozen product is soaked in ethanol, the soaked product is taken out and then thawed, and after thawing, it is soaked in hydrochloric acid to form a porous structure, thereby obtaining a three-dimensional porous chitosan / coal-based activated carbon composite sponge.
[0012] Preferably, the alkali activation comprises: heating a KOH solution to boiling, then adding coal powder and mixing, and sequentially drying and calcining to obtain activated coal; the calcination temperature is 400-800°C, and the insulation time is 2-4h; the usage ratio of the coal powder and the KOH solution is (0.1-1)g: (1-20)mL; the mass fraction of KOH in the KOH solution is 10-30%.
[0013] Preferably, the mass fraction of the KOH aqueous solution is 1-5%; the dosage ratio of the activated coal to the KOH aqueous solution is (1-5) g: (10-40) mL.
[0014] Preferably, the temperature of the hydrothermal reaction is 150-200° C., and the insulation time is 4-8 hours.
[0015] Preferably, the mass ratio of the coal-based activated carbon to P2O5 is 1:1; the dosage ratio of the coal-based activated carbon to methanesulfonic acid is (0.5-3) g: (2-16) mL; and the phosphorylation is carried out in an ice water bath.
[0016] Preferably, the mass ratio of the phosphorylated chitosan, chitosan and phosphorylated coal-based activated carbon is (0.1-0.5): (0.5-1): (0.1-1).
[0017] Preferably, the NH4HCO3 solution is obtained by dissolving NH4HCO3 in water; the mass fraction of NH4HCO3 in the NH4HCO3 solution is 10-20%, and the dosage ratio of the phosphated coal-based activated carbon and the NH4HCO3 solution is (0.1-1) g: (1-2) mL.
[0018] Preferably, the pH value of the hydrochloric acid is 3-5.
[0019] The present invention provides a three-dimensional porous chitosan / coal-based activated carbon composite sponge prepared by the preparation method described in the above scheme, and the surface of the sponge contains hydroxyl groups, amino groups and phosphoric acid groups.
[0020] The present invention provides the use of the three-dimensional porous chitosan / coal-based activated carbon composite sponge described in the above scheme as an adsorption material in adsorbing uranium in water.
[0021] The invention provides a method for preparing a three-dimensional porous chitosan / coal-based activated carbon composite sponge, comprising the following steps: alkali-activating coal powder to obtain activated coal; placing the activated coal in a KOH aqueous solution for hydrothermal reaction to obtain coal-based activated carbon; mixing the coal-based activated carbon, methanesulfonic acid and P2O5, phosphorylating the mixture to obtain phosphorylated coal-based activated carbon; mixing a phosphorylated chitosan aqueous solution, an acetic acid solution of chitosan, phosphorylated coal-based activated carbon and an NH4HCO3 solution, freezing the obtained mixture, soaking the obtained frozen product in ethanol, taking out the soaked product and then thawing it, and soaking it in hydrochloric acid after thawing to form a porous structure to obtain a three-dimensional porous chitosan / coal-based activated carbon composite sponge.
[0022] The surface of the three-dimensional porous chitosan / coal-based activated carbon composite sponge of the present invention has a large number of hydroxyl, amino and phosphoric acid groups, which are easy to combine with uranium ions to form complexes, thereby increasing the adsorption capacity of uranium. At the same time, the hydroxyl, amino and phosphoric acid groups work synergistically to improve the selective adsorption of uranium by the sponge in a vanadium-uranium mixed solution. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The effect of the initial pH value of the solution at different temperatures on the adsorption of uranium and the Zeta potential of PPCCS adsorbing U(VI) at different pH values;
[0024] Figure 2 is the effect of adsorbent dosage on uranium adsorption;
[0025] Figure 3 (a) shows the effect of contact time on the adsorption of U(VI) on PPCCS, with initial uranium concentration (C0) = 10, 50 and 100 mg·L -1 , the dosage of PPCCS is 45 mg, and the volume of uranyl ion solution (V) is 90 mL; (bd) are the adsorption isotherms of uranyl ions on PPCCS at (b) 288 K, (c) 298 K, and (d) 308 K;
[0026] Figure 4 In the figure, (a) is the partition coefficient of competing ions, and (b) is the partition coefficient of M-PPCCS, unphosphorylated sponge (PCCS), and PPCCS to vanadium and uranium;
[0027] Figure 5 PPCCS adsorption 10 mg·L at 15℃ -1 , SEM photos of uranium solution before and after pH=6;
[0028] Figure 6 PPCCS adsorption 10 mg·L at 15℃ -1 , EDS diagram after uranium solution with pH = 6;
[0029] Figure 7 is the X-ray surface scanning result of C, N, O, P and U on PPCCS after adsorption;
[0030] Figure 8 It is a two-dimensional (2-D) elemental map of the spatial distribution of mechanical properties of PPCCS;
[0031] Fig. 9 Contact angle test diagram of PCCS and PPCCS;
[0032] Fig.10 FT-IR spectra of functional groups in anthracite (PHA), PCCS and PPCCS composites after potassium hydroxide activation;
[0033] Fig.11 In the figure, (a) is the XPS spectra of PPCCS before and after uranium adsorption, (b) detailed XPS scans of C1s, N 1s, P 2p, and O1s of PPCCS before and after uranyl ion adsorption, and (f) detailed XPS graph of U4f of PPCCS before and after uranyl ion adsorption. DETAILED DESCRIPTION
[0034] The present invention provides a method for preparing a three-dimensional porous chitosan / coal-based activated carbon composite sponge, comprising the following steps:
[0035] Activating the coal powder with alkali to obtain activated coal;
[0036] Placing the activated coal in a KOH aqueous solution for hydrothermal reaction to obtain coal-based activated carbon;
[0037] The coal-based activated carbon, methane sulfonic acid and P2O5 are mixed and phosphorylated to obtain phosphorylated coal-based activated carbon;
[0038] A phosphorylated chitosan aqueous solution, an acetic acid solution of chitosan, phosphorylated coal-based activated carbon and an NH4HCO3 solution are mixed, the resulting mixture is frozen, the resulting frozen product is soaked in ethanol, the soaked product is taken out and then thawed, and after thawing, it is soaked in hydrochloric acid to form a porous structure, thereby obtaining a three-dimensional porous chitosan / coal-based activated carbon composite sponge.
[0039] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known in the art.
[0040] The present invention performs alkali activation on coal powder to obtain activated coal.
[0041] In the present invention, the coal powder is preferably obtained by crushing anthracite and then sieving it. In the present invention, the coal powder is preferably obtained by sieving it through a 100-mesh sieve.
[0042] In the present invention, the alkali activation preferably comprises: heating KOH to boiling, then adding coal powder to mix, and sequentially drying and calcining to obtain activated coal.
[0043] In the present invention, the amount ratio of the coal powder and the KOH solution is preferably (0.1-1) g: (1-20) mL, more preferably 0.5 g: 10 mL. In the present invention, the mass fraction of KOH in the KOH solution is preferably 10-30%. The present invention has no special requirements for the temperature of heating to boiling, and the KOH solution can be heated to boiling. In the present invention, the heating boiling time is preferably 1-2 hours. In the present invention, the mixing preferably includes ultrasound and stirring in sequence. The ultrasound time is preferably 1-2 hours, and the stirring time is preferably 4-6 hours. In the present invention, the drying temperature is preferably 60-100°C, more preferably 70-80°C. The present invention has no special requirements for the drying time, and it can be completely dried. After the drying, the present invention preferably grinds the dried product and then calcines it. In the present invention, the calcination temperature is preferably 400-800°C, more preferably 600-700°C, and the insulation time is preferably 2-4 hours, more preferably 3 hours. The present invention utilizes calcination to increase the specific surface area of coal powder.
[0044] After the calcination is completed, the present invention preferably further comprises washing the calcined product with distilled water until it becomes neutral, and drying it to obtain activated coal.
[0045] After obtaining activated coal, the present invention places the activated coal in a KOH aqueous solution for hydrothermal reaction to obtain coal-based activated carbon. In the present invention, the mass fraction of the KOH aqueous solution is preferably 1-5%. In the present invention, the dosage ratio of the activated coal to the KOH aqueous solution is preferably (1-5) g: (10-40) mL, more preferably (1-5) g: (20-30) mL. In the present invention, the temperature of the hydrothermal reaction is preferably 150-200°C, more preferably 160-180°C; the insulation time is preferably 4-8 hours, more preferably 5-6 hours. The present invention utilizes hydrothermal reaction to remove other impurities in anthracite and increase the specific surface area.
[0046] After the hydrothermal reaction is completed, the present invention preferably further comprises filtering the hydrothermal reaction product and retaining the solid on the filter paper, and drying at 80°C.
[0047] After obtaining the coal-based activated carbon, the present invention mixes the coal-based activated carbon, methane sulfonic acid and P2O5, and performs phosphorylation to obtain phosphorylated coal-based activated carbon.
[0048] In the present invention, the mass ratio of the coal-based activated carbon to P2O5 is preferably 1:1; the amount ratio of the coal-based activated carbon to methane sulfonic acid is preferably (0.5-3) g: (2-16) mL, more preferably 1 g: 7 mL. In the present invention, the methane sulfonic acid is used as a catalyst to catalyze the reaction between the coal-based activated carbon and P2O5.
[0049] In the present invention, mixing the coal-based activated carbon, methane sulfonic acid and P2O5 preferably comprises: placing the coal-based activated carbon in a container, then adding methane sulfonic acid, stirring evenly, and then adding P2O5 and stirring for 1 to 2 hours.
[0050] In the present invention, the phosphorylation is preferably carried out in an ice-water bath, and the phosphorylation is preferably carried out by standing in an ice-water bath for 2 to 3 hours. In the phosphorylation process of the present invention, phosphorus pentoxide reacts with -OH on anthracite to form phosphorylated anthracite; phosphorus pentoxide reacts with -OH on chitosan to form phosphorylated chitosan.
[0051] After the phosphorylation is completed, the product is washed three times with ether, acetone and methanol in sequence, and dried in an oven at 25-35° C. or naturally air-dried to obtain phosphorylated coal-based activated carbon.
[0052] After obtaining the phosphorylated coal-based activated carbon, the present invention mixes the phosphorylated chitosan aqueous solution, the chitosan acetic acid solution, the phosphorylated coal-based activated carbon and the NH4HCO3 solution, and freezes the obtained mixture.
[0053] In the present invention, the phosphorylated chitosan aqueous solution is preferably obtained by dissolving phosphorylated chitosan in water; the chitosan acetic acid solution is preferably obtained by dissolving chitosan in acetic acid. The present invention has no special requirements for the concentration of the phosphorylated chitosan aqueous solution, as long as the phosphorylated chitosan can be completely dissolved; the present invention has no special requirements for the concentration of the chitosan acetic acid solution, as long as the chitosan can be completely dissolved.
[0054] In the present invention, the mass ratio of the phosphorylated chitosan, chitosan and phosphorylated coal-based activated carbon is preferably (0.1-0.5): (0.5-1): (0.1-1), and more preferably (0.1-0.2): (0.7-1): 0.1. In the present invention, the NH4HCO3 solution is preferably obtained by dissolving NH4HCO3 in water; the mass fraction of NH4HCO3 in the NH4HCO3 solution is 10-20%, and the amount ratio of the phosphorylated coal-based activated carbon and the NH4HCO3 solution is (0.1-1) g: (1-2) mL.
[0055] In the present invention, mixing the phosphorylated chitosan aqueous solution, chitosan acetic acid solution, phosphorylated coal-based activated carbon and NH4HCO3 solution preferably comprises: mixing the phosphorylated chitosan aqueous solution, chitosan acetic acid solution and phosphorylated coal-based activated carbon, and then adding NH4HCO3 solution and stirring evenly. In the present invention, the freezing temperature is preferably -15°C to -20°C, and the freezing time is preferably 12 to 24 hours. The present invention ensures sponge formation by adding chitosan.
[0056] After the freezing is completed, the present invention soaks the frozen product in ethanol. The present invention has no special requirements for the amount of ethanol used, as long as the frozen product can be completely immersed. The present invention preferably soaks in ethanol twice, and the time of each soaking is preferably 30 to 40 minutes. The purpose of the first soaking in ethanol in the present invention is to thaw, and the second soaking is to replace water.
[0057] After the soaking in ethanol is completed, the soaked product is taken out and then thawed, and then soaked in hydrochloric acid to form pores to obtain a three-dimensional porous chitosan / coal-based activated carbon composite sponge.
[0058] The present invention does not have any special limitation on the thawing. In the present invention, the pH value of the hydrochloric acid is preferably 3 to 5; the present invention is preferably immersed in hydrochloric acid, and the immersion time is preferably 20 to 30 minutes. During the immersion in hydrochloric acid, the hydrochloric acid reacts with NH4HCO3 to release gas, forming a porous structure.
[0059] After soaking in hydrochloric acid, the present invention preferably washes the soaked product with deionized water until it is neutral, and dries it at room temperature to obtain a three-dimensional porous chitosan / coal-based activated carbon composite sponge.
[0060] The present invention provides a three-dimensional porous chitosan / coal-based activated carbon composite sponge prepared by the preparation method described in the above scheme, and the surface contains hydroxyl, amino and phosphate groups. In the present invention, the porosity of the three-dimensional porous chitosan / coal-based activated carbon composite sponge is 61.5842%. The median pore size (volume) under the conditions of 2.08psia and 1.103mL / g is 86891.66nm, and the median pore size (volume) under the conditions of 22.62psia and 0.167m 2 The median pore diameter (area) at 1.34 nm / g is 7994.52 nm.
[0061] The surface of the three-dimensional porous chitosan / coal-based activated carbon composite sponge of the present invention has a large number of hydroxyl, amino and phosphoric acid groups, which are easy to combine with uranium ions to form complexes, thereby increasing the adsorption capacity of uranium. At the same time, the hydroxyl, amino and phosphoric acid groups work synergistically to improve the selective adsorption of uranium by the sponge in a vanadium-uranium mixed solution.
[0062] The present invention provides the use of the three-dimensional porous chitosan / coal-based activated carbon composite sponge described in the above scheme as an adsorption material in the adsorption of uranium in water. In the present invention, the temperature of the water is preferably 15 to 35°C, more preferably 20 to 30°C; the pH value of the water is preferably 5 to 9, more preferably 6 to 8. In the present invention, the water is preferably seawater. In the present invention, the adsorption time is preferably 4 to 12 hours. The present invention has no special requirements for the specific method of the application, and the application method well known in the art can be used.
[0063] The three-dimensional porous chitosan / coal-based activated carbon composite sponge provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0064] Example 1
[0065] Use a high-speed universal grinder to crush the lump anthracite into powder, then pass it through a 100-mesh sieve to obtain coal powder; heat 10mL of a 20% KOH solution to boil for 1h, then add 0.5g of anthracite powder to the 20% KOH solution, ultrasonicate for 1h, magnetically stir for 4h, and place in a 100℃ oven to dry. After sufficient grinding, keep the temperature at 800℃ in a tube furnace for 2h, cool naturally to room temperature, take out and place in a beaker containing 1000ml of distilled water, stir fully, filter, wash to neutrality, and dry to obtain activated coal powder;
[0066] 5 g of activated anthracite was placed in 40 mL of 2% KOH aqueous solution, stirred evenly, poured into a reactor, placed in an electric heated blast drying oven for hydrothermal reaction at 200°C for 6 hours, the liquid was filtered and the solid on the filter paper was retained, and dried at 80°C to obtain coal-based activated carbon;
[0067] Take 2g coal-based activated carbon and put it in a beaker, add 14mL methane sulfonic acid and stir evenly, put it in a fume hood and add 2g P2O5, stir for 1h, put it in ice water and let it stand for 3h, then wash it three times with ether, acetone and methanol in sequence, and dry it in an oven at 25℃ to obtain phosphated coal-based activated carbon;
[0068] 0.173 g of phosphorylated chitosan (CSP) was dissolved in 4.25 mL of deionized water, 0.825 g of chitosan (CS) was dispersed in 4.25 mL of acetic acid (mass fraction 1%) solution and stirred evenly, then the two solutions were mixed and 0.1 g of phosphorylated coal-based activated carbon was added, 1.5 mL of NH4HCO3 (mass fraction of NH4HCO3 was 10%) solution was added, stirred for 60 s, frozen for 12 h, soaked in ethanol twice, each time for 30 minutes, and finally thawed, soaked in hydrochloric acid with a pH of 4 for 20 minutes, rinsed with deionized water to neutrality, and dried at room temperature to obtain a three-dimensional porous chitosan / coal-based activated carbon composite sponge, recorded as PPCCS sample.
[0069] Comparative Example 1
[0070] The unphosphorylated sponge (PCCS) was prepared as follows:
[0071] Use a high-speed universal grinder to crush the lump anthracite into powder, then pass it through a 100-mesh sieve to obtain coal powder; heat 10mL of a 20% KOH solution to boil for 1h, then add 0.5g of anthracite powder to the 20% KOH aqueous solution, ultrasonicate for 1h, magnetically stir for 4h, and place in a 100℃ oven for drying. After sufficient grinding, keep the temperature at 800℃ in a tube furnace for 2h, cool naturally to room temperature, take out and place in a beaker containing 1000ml of distilled water, stir fully, filter, wash to neutrality, and dry to obtain activated coal powder;
[0072] 5 g of activated anthracite was placed in 40 mL of 2% KOH aqueous solution, stirred evenly, poured into a reactor, placed in an electric heated blast drying oven for hydrothermal reaction at 200°C for 6 hours, the liquid was filtered and the solid on the filter paper was retained, and dried at 80°C to obtain coal-based activated carbon;
[0073] 0.825 g of chitosan (CS) was dispersed in 4.25 mL of acetic acid (mass fraction of 1%) solution and stirred evenly, 0.1 g of coal-based activated carbon was added, 1.5 mL of NH4HCO3 (mass fraction of NH4HCO3 was 10%) solution was added, stirred for 60 s, frozen for 12 h, soaked in ethanol twice, each time for 30 minutes, and finally thawed, soaked in hydrochloric acid with a pH of 4 for 20 minutes each time, soaked once, rinsed with deionized water until neutral, and dried at room temperature to obtain an unphosphorylated sponge, recorded as a PCCS sample.
[0074] Performance Testing:
[0075] Dissolve 0.2358 g U3O8 in a mixture of 2.705 mL nitric acid and 6 mL H2O2, and heat and dilute to obtain a uranyl nitrate stock solution (100 mg·L -1). The relevant stock solutions were diluted with distilled water to obtain uranium solutions of various concentrations used in the experiment.
[0076] The following experiment uses an adsorbent to adsorb 90 mL of uranium wastewater. By dropping sodium carbonate or 0.01-1 mol·L -1 The nitric acid solution was added to adjust the pH value of the uranium solution suspension to a range of pH 5.0 to 9.0. The adsorption process was carried out in a 100 mL centrifuge tube, which was placed in a constant oscillator and shaken at 175 rpm for 12 hours. After the experiment was completed, the solid matter was separated from the solution phase by filtration. Finally, the uranium concentration in the solution was analyzed by spectrophotometry. Removal efficiency (Re, %) and adsorption capacity (q e ,mg g -1 ) is calculated by equations (1) and (2).
[0077]
[0078]
[0079] In formula (1) and (2), C0, C e (mg·L -1 ) are the concentrations of uranium in the solution before and after adsorption. V(L) is the volume of the solution, and m(g) is the dry weight of the adsorbent. All adsorption experiments were performed in parallel, with an error within 5%.
[0080] Partition coefficient (K d ) is used to evaluate the selective adsorption of uranium by PPCCS. e (mg·L -1 ) are the concentrations of uranium in the solution before and after adsorption, V (mL) is the volume of the solution, and M (g) is the dry weight of the adsorbent.
[0081]
[0082] 1. Effect of initial pH value and initial uranium concentration
[0083] At three temperatures of 15, 25, and 35°C, the pH value range was 5.0 to 9.0 ± 0.1, and the PPCCS samples were tested for 10 mg·L -1 Adsorption efficiency of uranium solution. The temperature range of seawater is 15-35℃, and the average pH is about 8.3, so this temperature and pH range were selected for the experiment. As shown in the adsorption curve, PPCC has the best adsorption performance for uranium in the pH range of 6-8.
[0084] like Figure 1As shown in Figure 1, as the pH value increases from 5.0 to 9.0, the zeta potential of PPCCS gradually changes from positive to negative. When pH = 6.1, its zeta potential is 0, which means that pH = 6.1 is the isoelectric point of PPCCS. When the pH value of the solution is low, the main form of U(VI) in the solution is UO2 2+ At this time, the Zeta potential of PPCCS is positive, indicating that it is positively charged. Due to electrostatic repulsion, UO2 2+ It is not easy to be captured by PPCCS, and the adsorption efficiency is low. As the pH value of the solution increases, the surface functional groups of PPCCS begin to deprotonate and become negatively charged. At this time, U(VI) is mainly in the form of UO2 2+ 、UO2(OH) + 、(UO2)3(OH) 5+ and (UO2)2(OH)2 2+ The U(VI) exists in a positively charged form. Therefore, due to the strong electrostatic attraction, U(VI) is easily captured by the negatively charged adsorbent, which improves the adsorption efficiency. As the pH value continues to increase, the electrostatic attraction continues to increase, and PPCCS captures more and more U(VI), and finally the adsorption efficiency reaches a maximum at pH = 8.0. However, when the pH value is further increased, the presence of U(VI) in the solution becomes more complicated, although the surface of PPCCS is still negatively charged. (UO2)3(OH) 7- and UO2(OH)2 precipitation gradually increased at higher pH values, resulting in a decrease in the adsorption efficiency.
[0085] 2. Use different masses of adsorbents to adsorb 10 mg / L uranium solution for 12 hours (pH = 8, t = 25 ° C). The results of the effect of adsorbent on adsorption efficiency are as follows: Figure 2 As shown. With the increase of adsorbent concentration, the adsorption capacity of PPCCS for U(VI) ions continues to increase. When the mass of the adsorbent is less than 20 mg, the removal rate is less than 90%. When the amount of adsorbent reaches 30 mg, the removal rate reaches 99.86%. And with the further increase of adsorbent concentration, the adsorption rate does not increase significantly. This is because, during the adsorption experiment, when the amount of adsorbent added is small, there are fewer active sites for adsorbing ions, so the adsorption amount of U(VI) ions is also low; but since the concentration of U(VI) ions and other variables remain unchanged, the increase in amount means increasing the adsorption area and increasing the active adsorption sites, so the adsorption rate of U(VI) ions also increases accordingly.
[0086] 3. Effect of contact time and adsorption kinetics
[0087] Removal efficiency is a key factor in the practical application of adsorbents. Therefore, the present invention considers the adsorption of U(VI) on PPCCS as a function of adsorption time to discuss the adsorption kinetics. PPCCS was used to study the adsorption of 10 mg / L, 50 mg / L, and 100 mg / L uranium solutions at pH = 8 and 298 K. The results are as follows: Figure 2 As shown in (a). Figure 2 (a) shows that the adsorption of U(VI) by PPCCS from 0 to 4 h is the initial rapid adsorption stage, and after 4 h it is the gradual ion adsorption equilibrium stage. In the rapid adsorption stage, PPCCS has abundant adsorption sites, so the removal efficiency increases rapidly. However, as the adsorption proceeds, the number of adsorbents is constant, the free adsorption sites gradually decrease, and the removal efficiency gradually becomes constant. For three uranium solutions with different concentrations, the overall trend of PPCCS reaching adsorption equilibrium within 12 hours is consistent. Therefore, 12 h was used as the contact time for subsequent adsorption experiments.
[0088] 4. In order to evaluate the adsorption kinetics, the pseudo-first-order equation and pseudo-second-order equation were used to fit the adsorption kinetics of U(VI) on PPCCS. In the pseudo-first-order equation, adsorption is achieved through the diffusion and mass transfer of the adsorbate and is controlled by the diffusion rate of the adsorbate; while in the pseudo-second-order equation, adsorption is achieved through the chemical bonding between the adsorbate and the adsorbent, which is affected by the concentrations of both the adsorbate and the adsorbent.
[0089] ln(q e -q t )=ln q e -k1t (4)
[0090]
[0091] In the equation, q e (mg / g) and q t (mg / g) are the amount of U(VI) adsorbed by PPCCS at equilibrium and adsorption time t(min), respectively. k1(h -1 ), k2 (g / mg*h) are the adsorption rate constants of pseudo-first-order and pseudo-second-order respectively.
[0092] Table 1 Adsorption kinetic parameters of uranium on PPCCS
[0093]
[0094]
[0095] Different kinetic models are usually used to predict the adsorption mechanism and potential rate-controlling steps in solid-liquid systems. Here, two kinetic models were fitted to the adsorption experiments at three uranium concentrations. Figure 3The data in (a) and Table 1 show that the R 2 Higher than the R of the pseudo-first-order model 2 The pseudo-second-order kinetic model is more suitable for the adsorption kinetics of PPCCS and U(VI) ions than the pseudo-first-order kinetic model. This observation indicates that the adsorption of uranium on PPCCS is chemical adsorption rather than mass transfer. Chemical adsorption is related to temperature and uranium concentration.
[0096] 5. Adsorption isotherm
[0097] The initial uranium concentration was 10 mg·L -1 Up to 600mg·L -1 The adsorption isotherm at Figure 3 As shown in (bd). With the increase of the initial uranium concentration, the adsorption of U(VI) by PPCCS increased significantly, but the rate of increase in the adsorption amount continued to decrease until equilibrium was reached. 2 It is significantly higher than the Freundlich model, indicating that Langmuir is more suitable for fitting the adsorption isotherm, and the adsorption reaction mainly follows the monolayer adsorption mode. The results are shown in Table 2.
[0098] Table 2 Isotherm parameters of uranium adsorption on PPCCS
[0099]
[0100] 6. Adsorption thermodynamics
[0101] In order to understand the state characteristics of the adsorption process and evaluate the difficulty of adsorption, this section conducted adsorption experiments in the temperature range of 288, 298, and 308 K to study the effect of temperature on the adsorption of U(VI) by PPCCS. The relevant thermodynamic equations are as follows:
[0102] ΔG 0 =-RT ln K C (8)
[0103]
[0104] K C =1000K d (10)
[0105]
[0106] In the formula, K d is the solid-liquid partition coefficient (mg·L -1 ); T is the absolute temperature in Kelvin (K); R is the ideal gas constant (8.314 J mol-1K -1 ). dThe calculation formula is 11. The higher the temperature, the greater the solid-liquid partition coefficient. e is the adsorption capacity of uranium at equilibrium (mg g -1 );C e is the uranium concentration at equilibrium (mg·L -1 ). ΔH0, ΔS0 and ΔG0 are the enthalpy change, entropy change and Gibbs free energy change in thermodynamic parameters respectively.
[0107] Table 3 Adsorption thermodynamics of uranium on PPCCS
[0108]
[0109] The calculated thermodynamic parameters are shown in Table 3. From the data analysis in the table, ΔH0 is greater than zero, indicating that the adsorption process is endothermic. This may be because U(VI) forms various hydrated ions in the aqueous solution. Before adsorption, it needs to absorb heat to partially remove the hydration layer. The absorbed heat exceeds the heat released by the coordination and complexation of U(VI) ions with the adsorbent, so the overall nature is endothermic. ΔS0 is greater than zero, indicating that as the adsorption of U(VI) by PPCCS aerogel proceeds, the disorder of the solid-liquid interface in the system increases, which is beneficial to the complexation and stability of the adsorbent. At the three temperatures, ΔG0 is less than zero, and ΔG0 decreases with increasing temperature. It shows that the adsorption reaction of uranium by PPCCS aerogel is spontaneous, and higher temperatures are conducive to the adsorption reaction. If physical adsorption dominates the adsorption process, the increase in temperature will cause U(VI) ions to desorb from the adsorbent surface, so that the adsorption capacity decreases; conversely, if chemical adsorption dominates the adsorption process, the adsorption capacity will increase with increasing temperature. Therefore, the adsorption process of uranium by PPCCS aerogel is chemical adsorption. This may be because a chemical complex is formed between the active functional groups on its surface and U(VI). This complex forms a strong affinity for U(VI), making it difficult for U(VI) ions to desorb from the adsorbent surface even at higher temperatures. Instead, it is beneficial to increase the activity of the adsorbate ions and the adsorption reaction, and the adsorption capacity becomes larger.
[0110] 7. Effect of competing ions
[0111] Seawater usually contains a variety of cations, and these coexisting ions may affect the adsorption of U(VI). Therefore, it is necessary to study the selective adsorption of uranium by PPCCS in the presence of competing ions. The present invention studies the selective adsorption of U(VI) by PPCCS at pH = 8 and 25 °C. -1 )、V(0.02mg·L -1 )、Cu(0.025mg·L -1 )、Ca(0.4E3 mg·L -1)、Mg(1.3E3mg·L -1 )、Zn(0.04mg·L -1 )、Na(1.08E4 mg·L -1 ) and Cu(0.025mg·L -1 ) ions, the results are as follows Figure 4 As shown in (a). Figure 4 (a) shows the K of different competing ions. d , indicating that PPCCS has a strong ability to adsorb U(VI), indicating that PPCCS has a high adsorption selectivity for U(VI) ions in uranium aqueous solution containing multiple metal ions. In simulated seawater containing multiple metal ions, even in the presence of high concentrations of competing ions, PPCCS adsorbent still has a high selectivity for U(VI). Therefore, PPCCS has a good application prospect in uranium extraction from seawater.
[0112] 8. In order to study the synergistic effect of the PPCCS functional group on the adsorption performance of uranium and vanadium, the surface groups of PPCCS were modified by aminomethylation and hydroxyacetylation by acetic anhydride (specifically, 1 g of PPCCS was added to 150 mL of acetic anhydride, heated to reflux for 12 hours, and washed with deionized water for later use), thereby masking the role of the corresponding groups in adsorption (referred to as M-PPCCS). The infrared spectrum of M-PPCCS was compared with that of PPCCS, and corresponding changes were found in the infrared spectrum of M-PPCCS, indicating that the masking was successful. The adsorption of vanadium-uranium mixed solution by M-PPCCS, unphosphorylated sponge (PCCS) and PPCCS is shown in Figure 2. Figure 4 As shown in (b), the results show that after masking the hydroxyl and amino groups (M-PPCCS), the distribution coefficients of uranium and vanadium are reduced to 4430.77 mL·g -1 and 98.87 mL·g -1 , a difference of 44.8 times; the distribution coefficient of uranium in the unphosphorylated sponge material (PCCS) increased significantly, while the distribution coefficient of vanadium increased only slightly; the phosphated sponge material (PPCCS) can further increase the distribution coefficient of uranium. The distribution coefficients of uranium and vanadium are 13980.469 mL·g -1 and 220.859 mL·g -1 , the ratio can reach 63.3. The results show that in the presence of uranium and vanadium, the synergistic effect of hydroxyl, amino and phosphate groups can significantly improve the adsorption selectivity of uranium to PPCCS.
[0113] 9. Adsorption mechanism and characterization
[0114] Mercury intrusion analysis was performed on PPCCS. The results show that the porosity of PPCCS is 61.5842%.-1 The median pore size (volume) under the conditions is 86891.66nm, at 22.62psia and 0.167m 2 ·g -1 The median pore size (area) is 7994.52 nm. The increase in porosity is beneficial to the adsorption of the material, because the higher the porosity, the stronger the adsorption capacity.
[0115] Figure 5 It shows that PPCCS adsorbs 10 mg·L at 15 °C -1 , SEM photos of uranium solution before and after pH=6 (left: before adsorption, right: after adsorption). There are some irregular pores on the surface of PPCCS before adsorption. After adsorption of U(VI), the surface pores of PPCCS are filled and there are slight protrusions on the surface. After the material adsorbs U(VI), the element content is analyzed by EDS. Figure 6 As shown. In general, in addition to the original C, O, P and N in the material, 31.76wt% U(VI) was detected. These results indicate that part of U(VI) was adsorbed by the PPCCS material and that the functional groups on the material participated in the adsorption process. The X-ray surface scan results of C, N, O, P and U on PPCCS after adsorption are shown in Figure 7 As shown in the figure, the distribution areas of O, P, C, N and the whole surface are largely consistent. The adsorbed U is also basically evenly distributed on the surface of PPCCS, further indicating that PPCCS is involved in the adsorption process. U(VI) may be deposited in the irregular pores of PPCCS, or it may interact with the phosphate, amino and hydroxyl groups on the surface of PPCCS. In addition, from Figure 8 It can be seen that when an external force of 50 g is applied to the multidimensional porous structure PPCCS, the shape of the PPCCS sponge immediately returns to its original state after the external force disappears, indicating that the PPCCS sponge has sufficient structural strength, which is conducive to long-term use in seawater.
[0116] 10. The structure of PPCCS is loose and rough, which can greatly improve its hydrophilicity. Therefore, it provides a good conductive channel for uranyl ions. In addition, the surface of PPCCS is rich in phosphate, hydroxyl and amino groups, which can easily react with U(VI) to form a complex. At the same time, the phosphate obtained by phosphorylation of PPCCS can also complex with uranium ions. The hydrophilicity of PPCCS was tested by water contact angle experiment, such as Fig. 9 As shown. The hydrophilicity of PPCCS is stronger than that of the unphosphorylated sponge (PCCS). The contact angle of PPCCS is 75.1°, reaching 70.18° compared to PCCS. This indicates that phosphorylation significantly improves the hydrophilicity of the PPCCS sponge.
[0117] 11. FT-IR spectra of functional groups in anthracite (PHA), PCCS and PPCCS composites after potassium hydroxide activation Fig.10 The peaks appear at 3458, 2885, 1638, 1419, 1382, 1154, 1093, and 892 cm -1 PCCS and PPCCS composites have a peak at 3458 cm -1 The phenolic hydroxyl group–OH -1 , at 3440cm -1 The absorption band near the peak shows a trend of broadening and shifting to the low frequency region (blue shift), which is due to the superposition of -OH groups, -NH2 functional groups and OH bond interactions in the system, which also means that the formation of PPCCS composite materials is related to the OH bond interactions in the system. The peak is 2883cm -1 It is due to the vibration of the CH bond in the methylene group, at 1419 cm -1 , which is the stretching vibration of -CH2. The stretching vibration of the acylated carbonyl group and the bending vibration of -NH2 appear at 1638cm -1 Nearby. At 1154cm -1 A peak from the P=O structure appeared at 1093 cm -1 The peak from the POC structure is 892 cm -1 The peak from the POH structure is at 440 nm, indicating that PCCS has been successfully phosphorylated. The enhancement of the PPCCS peak is due to the increased hydrophilicity of the sponge caused by phosphorylation.
[0118] 12. Fig.11 (a) shows the XPS spectra of PPCCS before and after uranium adsorption. By comparing the chemical analysis and XPS results of PPCCS before and after uranium adsorption, the adsorption mechanism of PPCCS on uranyl ions is revealed. Fig.11 As can be seen in (a), the peak intensities of C 1s, O1s and N1s decrease in turn. Fig.11 (b) Detailed scan of C 1s XPS shows a double peak binding energy spectrum corresponding to 283 and 284.8 eV binding energies, respectively. The peak near 284.80 eV is the C=C / CC peak of the SP2 or SP3 hybrid form in the sponge structure. The peak near 286.3 eV represents the CO structure, revealing the form of carbon atoms and oxygen atoms in the sponge. The peak near 285.67 eV represents the CN structure. Fig.11 (c) is the XPS image of N1s3. The atomic mass of N before and after adsorption is 4.78% and 7.36%, respectively, and the peak binding energy is 399.38 and 399.88 eV, respectively. XPS ( Fig.11The spectrum in (d) shows a peak at about 130.6 eV, representing P 2p, indicating that the sponge has been successfully phosphorylated. The p2p peak area increases after adsorption, indicating that PO forms a complex with U(VI). At the same time, the peak areas of -NH2 and -OH decrease, indicating that -NH2 and -OH are also involved in the adsorption process. At the same time, the O1s peak was observed at 532.08 eV. The presence of hydrophilic groups such as epoxy, hydroxyl and OvC groups is confirmed. In addition, a peak representing PO was found at 531.00 eV. These results are consistent with those obtained by FT-IR. From the XPS spectra before and after adsorption, it can be seen that the adsorption of uranyl ions on PPCCS ( Fig.11 (f)). The two peaks at 378.63 and 388.92 eV in the figure are characteristic peaks of uranium ions, namely U 4f7 and U 4f5, respectively. This shows that PPCCS adsorbs uranium in the form of U(VI). From these experiments, it can be seen that the complexation of U(VI) with phosphates, hydroxyls and amino groups on the surface of PPCCS is the main mechanism of U(VI) adsorption. At the same time, the irregular pores of PPCCS can increase the surface adsorption capacity of PPCCS. Chitosan itself contains a large number of hydroxyl and amino functional groups. These groups play an important role in the adsorption of uranium by PPCCS and are fully utilized in the adsorption process. The hydroxyl and amino active centers on the surface of PPCCS form relatively stable complexes with U(VI).
[0119] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a three-dimensional porous chitosan / coal-based activated carbon composite sponge, characterized in that: The following steps are involved: Activating the coal powder with alkali to obtain activated coal; Placing the activated coal in a KOH aqueous solution for hydrothermal reaction to obtain coal-based activated carbon; The coal-based activated carbon, methane sulfonic acid and P2O5 are mixed and phosphorylated to obtain phosphorylated coal-based activated carbon; A phosphorylated chitosan aqueous solution, an acetic acid solution of chitosan, a phosphorylated coal-based activated carbon and an NH4HCO3 solution are mixed, the resulting mixture is frozen, the resulting frozen product is soaked in ethanol, the soaked product is taken out and then thawed, and the thawed product is soaked in hydrochloric acid to form a porous structure, thereby obtaining a three-dimensional porous chitosan / coal-based activated carbon composite sponge; The mass ratio of the phosphorylated chitosan, chitosan and phosphorylated coal-based activated carbon is (0.1-0.5): (0.5-1): (0.1-1).
2. The preparation method according to claim 1, characterized in that: The alkali activation comprises: heating a KOH solution to boiling, then adding coal powder and mixing, and sequentially drying and calcining to obtain activated coal; the calcination temperature is 400-800°C, and the insulation time is 2-4 hours; the usage ratio of the coal powder and the KOH solution is (0.1-1) g: (1-20) mL; and the mass fraction of KOH in the KOH solution is 10-30%.
3. The preparation method according to claim 1, characterized in that: The mass fraction of the KOH aqueous solution is 1-5%; the dosage ratio of the activated coal to the KOH aqueous solution is (1-5) g: (10-40) mL.
4. The preparation method according to claim 1 or 3, characterized in that: The temperature of the hydrothermal reaction is 150-200° C., and the insulation time is 4-8 hours.
5. The preparation method according to claim 1, characterized in that: The mass ratio of the coal-based activated carbon to P2O5 is 1:1; the usage ratio of the coal-based activated carbon to methanesulfonic acid is (0.5-3) g: (2-16) mL; and the phosphorylation is carried out in an ice water bath.
6. The preparation method according to claim 1, characterized in that: The mass fraction of NH4HCO3 in the NH4HCO3 solution is 10-20%, and the usage ratio of the phosphated coal-based activated carbon to the NH4HCO3 solution is (0.1-1) g: (1-2) mL.
7. The preparation method according to claim 1, characterized in that: The pH value of the hydrochloric acid is 3-5.
8. The three-dimensional porous chitosan / coal-based activated carbon composite sponge prepared by the preparation method according to any one of claims 1 to 7 has hydroxyl groups, amino groups and phosphoric acid groups on its surface.
9. Use of the three-dimensional porous chitosan / coal-based activated carbon composite sponge according to claim 8 as an adsorption material for adsorbing uranium in water.
